Some new conditions for weighted Fourier inequality - Akhatkulov, Sokhobiddin; Abubakar, Mohamed (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
In this paper we give some new conditions on weigh u and v for weighted Fourier transform norm inequality ||f||q,u ≤ C||f||p,v in case 1 < p,q < ∞.